Biological imaging of challenging targets: Peripheral nerve, mouse bones and cultured osteoclasts - Alanne, Maria (fi=Turun yliopisto|en=University of Turku|, 2021)
During this study, advances in bioimaging have affected the biomedical research field. In this thesis, traditional microscopy and selected new techniques, namely microcomputed tomography (µCT), STED microscopy and laser-capture microdissection have been combined to study complex tissues in human adults such as developing peripheral nerves, bones and osteoclasts to reveal previously unseen features of these tissues and cells. Confocal microscopy was used to analyze the adult and developing human peripheral nerves. Tight junction proteins were localized to subcellular structures of myelinating Schwann cells. The combination of tight junction proteins differed from that of rodents. Furthermore, claudin expression was weak in fetal endoneurium during the second trimester, and the junctions were not fully maturated by the end of the third trimester. The results suggest that the maturation of Schwann cell autotypic junctions continues after birth. Various imaging modalities were combined in order to analyze the phenotype of the Nf1Ocl mouse model. µCT revealed narrowed growth plates and slight differences in trabecular and cortical bone in NfOcl-/- mice, but not in the osteoporotic bone phenotype. However, in vitro studies showed accelerated bone resorption capacity and a hyperactivated Ras signaling pathway in Nf1-/- osteoclasts. STED microscopy uncovered new features of actin, as bending and branching filaments were demonstrated in human osteoclasts. New features of actin filaments were detected also in macrophages and keratinocytes. The results emphasize the importance of bioimaging techniques in studying challenging tissues.

Biokuvantamisen haastavat kohteet: erifeerinen hermo, luu ja osteoklastiviljelmät Väitöskirjassa tutkittiin vaikeasti kuvannettavia kudoksia, aikuisen ja kehittyvän sikiön perifeerista hermoa, luuta sekä osteklasteja yhdistämällä tavanomaisia kuvantamismenetelmiä valikoitujen mikroskopian erityismenetelmien kanssa. Aikuisen ja kehittyvän sikiön perifeerinen hermo kuvannettiin konfokaali-mikroskopialla. Tiiviit liitokset sijaitsivat solunsisäisissä rakenteissa myeliiniä tuottavissa soluissa. Tulokset eroavat aiemmin jyrsijöillä tehtyihin havaintoihin nähden. Tiivisliitosproteiini klaudiinin ilmentyminen oli vähäistä toisen raskauskolmanneksen aikana, eivätkä tiiviit liitokset ehtineet kehittyä loppuun asti viimeisen kolmanneksen loppuun mennessä. Todennäköisesti tiiviit liitokset kehittyvät vielä syntymän jälkeen. Ehdollisesti poistogeenisen Nf1Ocl -hiirimallin ilmiasua tutkittiin yhdistämällä useita kuvausmodaliteetteja. Mikrotietokonetomografian avulla havaittiin sääriluussa kasvulevyn madaltuneen sekä kuoriluussa että hohkaluussa havaittiin useita pieniä muutoksia, mutta vastoin olettamusta kudoksessa ei todettu luukatoon viittaavaa. Soluviljelyolosuhteissa Nf-/- osteoklastit hajoittivat aggressiivisesti luuta sekä niiden Ras-signaalireitti oli aktivoitunut. STED mikroskoopin avulla paljastui uusia aktiinin ominaisuuksia. Aktiinin havaittiin taipuvan ja haarautuvan ihmisen osteoklasteissa sekä muissa solutyypeissä, makrofageissa ja keratinosyyteissä. Nämä tulokset korostavat biokuvantamisen tekniikan tärkeyttä varsinkin, kun kohteena on haastava kudos.